Arecoline improves vascular endothelial function in high fructose-fed rats via increasing cystathionine-γ-lyase expression and activating KATP channels - Ling Hong-yan; Wang Guang; Zhang Wei; Li Xing; Zhou Shou-hong; Hu Bi (Acta Pharmacologica Sinica; Vol 33, No 8 (August 2012): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of arecoline, a major component of betel nut, on vascular endothelial function in high fructose-fed rats and the potential mechanisms underlying the effect. Methods: Male Wistar rats were fed a high-fructose or control diet for 16 weeks. At the beginning of week 13, the rats were injected ip with low (0.5 mg·kg−1·d−1), medium (1.0 mg·kg−1·d−1) or high (5.0 mg·kg−1·d−1) doses of arecoline for 4 weeks. At the termination of the treatments, blood was collected, fasting blood glucose (FBG) and serum insulin (FSI) levels were measured, and insulin sensitivity index (ISI) was calculated. The thoracic aortas were isolated and aortic rings were prepared for studying ACh-induced endothelium-dependent vasorelaxation (EDVR). The mRNA and protein expression of cystathionine-γ-lyase (CSE) in the thoracic aortas was analyzed using RT-PCR and Western blot analysis, respectively. Results: In high fructose-fed rats, the levels of FBG and FSI were remarkably increased, whereas the ISI and the mRNA and protein expression of CSE were significantly decreased. ACh-induced EDVR in the aortic rings from high fructose-fed rats was remarkably reduced. These changes were reversed by treatment with high dose arecoline. Pretreatment of the aortic rings rings from high fructose-fed rats with the CSE inhibitor propargylglycine (10 mmol/L) or the ATP-sensitive potassium (KATP) channel blocker glibenclamide (10 mmol/L) abolished the restoration of ACh-induced EDVR by high dose arecoline. On the contrary, treatment with high dose arecoline significantly impaired ACh-induced EDVR in the aortic rings from control rats, and pretreatment with propargylglycine or glibenclamide did not cause further changes. Conclusion: Arecoline treatment improves ACh-induced EDVR in high fructose-fed rats, and the potential mechanism of action might be associated with increase of CSE expression and activation of KATP channels by arecoline.